Renewable Poly(butene 2, 5-furan dicarboxylate) Nanocomposites Constructed by TiO2 Nanocubes: Synthesis, Crystallization, and Properties. (July 2021) - Zhou, Guannan; Li, Lu; Jiang, Min; Wang, Guoqiang; Wang, Rui; Wu, Guangfeng; Zhou, Guangyuan
Highlights: The crystallization rate of PBF can be promoted by TiO2 nanocubes, and the fastest half-crystallization time is less than 1 minute. In addition to improving the crystallization rate, the TiO2 nanocubes also promoted the elongation at break of PBF. The TiO2 nanocubes reduced the UV transmittance of PBF to less than 5%. Abstract: Poly(butene 2, 5-furan dicarboxylate) (PBF) is an emerging bio-based polyester with excellent thermal and tensile properties. It is expected to replace its petroleum-based homologous polyester, polybutylene terephthalate (PBT). However, the crystallization rate and strength of PBF need to be improved. In this study, PBF/TiO2 nanocomposites were synthesized by the in-situ polymerization of 2, 5-furandicarboxylic acid (FDCA), butanediol, and rutile/anatase TiO2 nanocubes, with a size of 50 nm. The amount of nano-TiO2 added was 1–9‰ of the mass ratio of FDCA. As a result, a series of PBF/TiO2 nanocomposites with high molecular weights was obtained. The crystallization rate of the nanocomposites was significantly improved compared to that of pure PBF. The isothermal and non-isothermal crystallization of the nanocomposites were tested, and the temperature and rates of crystallization were compared. The shortest half-crystallization time was less than 1 min. It is evident from the results that the crystallization rate of the composite increases with an increase in the nano-TiO2 content and reaches a maximum at a nano-TiO2 content of 7‰. In addition, the elongation at break and impact strength of the nanocomposites increased by 118% and 200%, respectively, compared to that of neat PBF. In the range of 200–400 nm, the lowest UV transmittance of nanocomposites is only 5%, which is highly beneficial for the application of PBF in the field of film packaging. Graphical abstract: Image, graphical abstract